Electronic and optical properties of a-c from tight-binding molecular dynamics simulations - Kopidakis, Georgios; Kelires, Pantelis C.; Mathioudakis, Christos (My University, 2005)
Although the structural and mechanical properties of a-C have been theoretically investigated in detail, this is not so for the optoelectronic properties. Many issues remain unclear, such as the influence of disorder and intrinsic defects on the localization of the electron states and on the optical transitions. Here, as a first step towards solving this kind of problems, we present a computational approach to the study of the optoelectronic properties of a-C. This is based on tight-binding (TB) molecular dynamics (TBMD) simulations using a reliable environment-dependent Hamiltonian. The a-C networks were generated by quenching from the liquid. The electronic density of states of all simulated networks show that the material is semiconducting, and that the gap is clearly controlled by the separation of the π and π* peaks. A Tauc gap analysis shows that the optical gap varies between 2.7 and 0.3 eV. We analyze the dielectric functions as a function of the sp3 fraction. We also compare the computational results with experimental dielectric function spectra revealing considerable consistency between theory and experiment.
Keywords: Computer simulation; Dielectric properties; Ellipsometry; Molecular dynamics; Molecular dynamics